The effectiveness of a standardised rapid response system on the reduction of cardiopulmonary arrests and other adverse events among emergency surgical admissions - Ou, Lixin; Chen, Jack; Hillman, Ken; Flabouris, Arthas; Parr, Michael; Green, Malcolm (Resuscitation, 2020)
A standardised rapid response system (RRS), called the “Between-the-Flags” (BTF) program, was implemented across a large health jurisdiction in Australia in 2010. The impact of RRS on emergency surgical admissions is unknown. We linked the NSW Admitted Patient Data Collection (APDC) and the NSW Registry of Births, Deaths, and Marriages. We used a propensity score-based inverse-probability-weighting adjustment to estimated average treatment effects among treated subjects (prior-RRS hospitals vs prior-non-RRS hospitals) before the BTF implementation (2007–2008) and after (2010–2013). Before BTF, prior-RRS hospitals had a lower rate of in hospital cardiopulmonary arrests (IHCA) (4.7 vs 7.8 per 1000 admissions, P < 0.001), a lower rate of IHCA related deaths (3.0 vs 4.4 per 1000 admissions, P = 0.03) compared with patients in prior-non-RRS hospitals. There were no significant differences in overall in-hospital mortality and 30-day mortality between the two cohorts. After BTF, there were no significant differences for IHCA (4.8 vs 5.5 per 1000 admissions, P = 0.081) and related death rates (2.4 vs 2.3 per 1000 admissions, P = 0.678) between the two cohorts. Hospital mortality, 30-day mortality improved across both prior-RRS and prior-non-RRS hospitals following the BTF implementation. BTF program was associated with a significant reduction in IHCA and IHCA deaths for emergency surgical patients in prior-non-RRS hospitals but not in the prior-RRS hospitals. The overall hospital and 30-day mortality improved in both cohorts after BTF.